URGENSI PENGUASAAN KONSEP DASAR BAHASA INDONESIA BAGI MAHASISWA PENDIDIKAN DI ERA DIGITAL - Nugraha, Eggie; Muhammad Faizal; Acep Roni Hamdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mastery of basic concepts of the Indonesian language plays a crucial role in supporting the academic and professional success of education students, particularly in the digital era characterized by the rapid development of information and communication technology. The digital era has brought significant changes to students’ language practices, which are indicated by the increasing use of informal language and the neglect of linguistic norms in academic contexts. This study aims to examine the urgency of mastering basic concepts of the Indonesian language for education students in the digital era and its implications for strengthening academic literacy and the professional readiness of prospective teachers. This research employs a qualitative approach using a library research method through the analysis of reference books, scholarly journal articles, and relevant educational policy documents. The findings indicate that mastery of basic Indonesian language concepts serves as a foundation for academic literacy that influences critical thinking skills, argumentative ability, and linguistic accuracy among education students. Furthermore, digital literacy that is not supported by strong conceptual language understanding has the potential to reduce the quality of academic language. Therefore, strengthening the mastery of basic Indonesian language concepts in higher education is a strategic necessity to prepare education students who are adaptive, critical, and professionally competent in the digital era.